Physical Properties and Selective CO Oxidation of Coprecipitated CuO/CeO2 Catalysts Depending on the CuO in the Samples - Akkarat Wongkaew; Wichai Kongsi; Pichet Limsuwan (Advances in Materials Science and Engineering)
This paper investigates the effects of CuO contents in the CuO-CeO2 catalysts to the variation in physical properties of CuO/CeO2 catalysts and correlates them to their catalytic activities on selective CO oxidation. The characteristic of crystallites were revealed by X-ray diffraction, and their morphological developments were examined with TEM, SEM, and BET methods. Catalytic performance of catalysts was investigated in the temperature range of 90–240°C. The results showed that the catalyst was optimized at CuO loading of 20 wt.%. This was due to the high dispersion of CuO, high specific surface area, small crystallite sizes, and low degree of CuO agglomeration. Complete CO conversion with near 100% selectivity was achieved at a temperature below 120°C. The optimal performance was seen as a balance between CuO content and dispersion observed with growth, morphology, and agglomeration of nanostructures.